Extraction optimization, purification and immunostimulatory activity in vitro of polyphenols from apple (Malus domestica) peel - Riaz, Asad; Yousaf, Khurram; Mohamed Abdin; Jabbar, Saqib; Muhammad Abid; Muhammad Hashim, Malik
Apple peel polyphenols were extracted by ultrasound-assisted extraction (UAE) and conditions for the extraction of polyphenols were optimized by the response surface methodology. The optimized conditions determined as 32 min of extraction time, 29 °C of extraction temperature and ethanol concentration of 56% with a yield of 35.08 ± 0.26 mg gallic acid equivalent/g dry weight. Six resins were used for the purification and D101 resin showed the highest ratio of desorption for polyphenols and further applied for dynamic adsorption/desorption test. Catechin, procyandin B, querecitin-3-galactoside and querecitin xyloside were identified in purified polyphenols by HPLC-MS/MS. Finally, the immunostimulatory activity in vitro of purified polyphenols on RAW264.7 cell lines was evaluated. The apple peel polyphenols exhibited a dose-dependent effect (p < 0.05) on the strongest propagation of RAW264.7 cells. The results demonstrate that apple peel is a valuable source of polyphenols and could be used as a natural immunostimulating agent for application in functional foods.